Yogurt in the prevention of diabetes mellitus - Varon, Joseph (World Nutrition Journal, 2024)
Yogurt, a popular fermented dairy product, is lauded for its nutritional benefits and role in promoting gut health. Recent studies have highlighted its potential in preventing chronic diseases, including type 2 diabetes mellitus (T2DM). This abstract delves into the mechanisms through which yogurt exerts its beneficial effects and explores how its regular consumption may contribute to diabetes prevention. Yogurt is rich in essential nutrients such as calcium, vitamin D, protein, and probiotics. The probiotics, particularly strains of Lactobacillus and Bifidobacterium, play a crucial role in maintaining gut microbiota balance. These live bacteria contribute to improved digestion and enhance immune function, pivotal in managing and preventing metabolic disorders like T2DM.